Injection‐molded capsular device for oral pulsatile release: Development of a novel mold. Issue 2 (18th November 2012) - Zema, Lucia; Loreti, Giulia; Macchi, Elena; Foppoli, Anastasia; Maroni, Alessandra; Gazzaniga, Andrea
Abstract The development of a purposely devised mold and a newly set up injection molding (IM) manufacturing process was undertaken to prepare swellable/erodible hydroxypropyl cellulose‐based capsular containers. When orally administered, such devices would be intended to achieve pulsatile and/or colonic time‐dependent delivery of drugs. An in‐depth evaluation of thermal, rheological, and mechanical characteristics of melt formulations/molded items made of the selected polymer (Klucel® LF) with increasing amounts of plasticizer (polyethylene glycol 1500, 5%–15% by weight) was preliminarily carried out. On the basis of the results obtained, a new mold was designed that allowed, through an automatic manufacturing cycle of 5 s duration, matching cap and body items to be prepared. These were subsequently filled and coupled to give a closed device of constant 600 μm thickness. As compared with previous IM systems having the same composition, such capsules showed improved closure mechanism, technological properties, especially in terms of reproducibility of the shell thickness, and release performance. Moreover, the ability of the capsular container to impart a constant lag phase before the liberation of the contents was demonstrated irrespective of the conveyed formulation. © 2012 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:489–499, 2013